Neurodegenrative changes in retina of rats with streptozotocin-induced diabetes under conditions of treatment with niacin-oxy-ethylidene-diphosphonate germanate (MIGU-4) - V.I. Kresyun; N. Al-Nadawi (Ukrainian Society of Ophthalmologists, 2023)
Background: Diabetes is accompanied by neurodegenerative changes in the retina. The determination of retinal function parameters under conditions of experimental diabetes may allow for the development of new approaches to pharmacological vision correction. Purpose: To assess changes in the metabolic (lipid peroxidation and antioxidant defence) and functional characteristics (electroretinography (ERG)) of the retina in the rat with streptozotocin (STZ)-induced diabetes, treated with niacin-oxy-ethylidene-diphosphonate germanate (MIGU-4) and a reference drug, diazepam. Material and Methods: Diabetes was induced intraperitoneally (i.p.) in Wistar male rats by streptozotocin (STZ 65 mg/kg). Four weeks thereafter, the rats received a two-week course of a daily dose of MIGU-4 (5.0 mg/kg or 25.0 mg/kg) or diazepam (0.5 mg/kg or 1.5 mg/kg). The electroretinogram (ERG) was obtained, the animals were euthanized and retinal malondialdehyde (MDA) levels and superoxide dismutase (SOD) and catalase (CAT) activity were determined. Results: In rats with untreated STZ-induced diabetes, the retinal MDA level was 3.71 times increased and CAT activity was 35% lower, compared to controls, whereas the SOD activity was half of the activity found in controls (р < 0.05). In diabetic animals treated with MIGU-4 i.p. at a 25.0-mg/kg daily dose, the retinal MDA level was 63.2% lower, whereas the CAT activity and SOD activity were 41.9% and 27.6%, respectively, higher, than in untreated diabetic rats (р < 0.05). In diabetic animals treated with diazepam i.p. at a 1.5-mg/kg daily dose, the retinal MDA level was 59.2% lower, whereas the CAT activity and SOD activity were 44.4% and 32.1%, respectively, higher, than in untreated diabetic rats (р < 0.05). In untreated diabetic rats, the ERG b-wave amplitude was 39.2% lower, ERG a-wave and b-wave latencies, 23.4% and 14.0%, respectively, higher, and the a-wave amplitude recovery rate, 38.8% lower than in controls (р < 0.05). The use of a 25.0-mg/kg daily dose of MIGU-4 resulted in a 29.7% and 33.9%, respectively, increase in the ERG b-wave amplitude and the a-wave amplitude recovery rate compared to untreated diabetic rats (р < 0.05). The use of a 1.5-mg/kg daily dose of diazepam resulted in a 25.0% and 30.0%, respectively, increase in the above ERG parameters compared to untreated diabetic rats (р < 0.05). In untreated diabetic rats, the number of squares crossed (SK) was 29.4% lower (р < 0.05); the number of central squares crossed (CSC), 52.1% lower (р < 0.05); the number of upright postures (UP), 34.2% lower; and the defecation bolus number, 32.4% higher than in controls (р < 0.05). After MIGU-4 (25-mg/kg) withdrawal, there were no more differences in SK, CSC, UP and defecation bolus numbers between treated diabetic rats and controls. In addition, the number of CSC was 4.27 times lower than in controls, and half of that in untreated diabetic animals (р < 0.05). In diabetic rats treated with diazepam, the number of UP was 2.56 times lower than in controls (р < 0.05), and 40.7% lower than in untreated diabetic rats (р < 0.05), whereas the defecation bolus number was 40.5% higher than in controls (р < 0.05). Conclusion: STZ-induced diabetes is accompanied by an impairment of the oxidant/ antioxidant balance in the retina with an increase in retinal MDA, decrease in retinal SOD and CAT activity, and ERG abnormalities such as reduced ERG amplitude and increased ERG latency. A course treatment with niacin-oxy-ethylidene-diphosphonate germanate (MIGU-4) i.p. at a daily dose of 25.0 mg/kg provides for a decrease in retinal MDA and an increase in retinal SOD and CAT activity and ERG wave amplitude The withdrawal of a two-week treatment with MIGU-4 i.p. at a daily dose of 25.0 mg/kg decreased open-field anxiety-like behaviors, whereas the withdrawal of a two-week treatment with diazepam i.p. at a daily dose of 1.5 mg/kg increased open-field anxiety-like behaviors. The corrective effect of treatment with MIGU-4 corresponds to the corrective effect of treatment with diazepam.